Design and implementation of an IoT-based e-learning testbed. (2017) - Oda, Tetsuya; Matsuo, Keita; Barolli, Leonard; Yamada, Masafumi; Liu, Yi
Owing to the opportunities provided by the internet, people are taking advantage of e-learning courses and many research efforts have been dedicated to the development of e-learning systems. So far, many e-learning systems are proposed and used practically. However, in these systems the e-learning completion rate is low. One of the reasons is the low study desire and motivation. In this work, we design and implement an IoT-based e-learning testbed using Raspberry Pi mounted on Raspbian. We analyse the performance of Optimised Link State Routing (OLSR) and Wired Equivalent Privacy (WEP) protocol in an indoor scenario. For evaluation we considered throughput, delay and jitter metrics. The experimental results show that the nodes in the testbed were communicating smoothly.